District Director of Agriculture in Ghana Survey - International Food Policy Research Institute (International Food Policy Research Institute, 2020)
This data is from a study conducted with 80 directors of agriculture in Ghana’s Metropolitan, Municipal, and District Assemblies (MMDAs). The aim of the survey was to identify how the devolution of agriculture functions to the MMDAs since 2012 has affected their job functions and ability to provide agricultural services to the communities in which they work. The survey is split into 9 modules: 1. Location (LN) – preliminary characteristics of the location where the DDA is employed; the gender of the respondent is also recorded in this module 2. General Information (ID) – basic demographic and educational background, as well as the length of time the director has served in the MMDA 3. Employment History (EH) – details on the current job, number of previous jobs, district location of previous jobs, job experiences, and aspirations within the civil service 4. Agricultural Planning and Implementation (AP) – questions related to the agricultural planning process within the district 5. Agricultural Budgets and Expenditures (AB) – details on the agricultural budgeting and expenditure process 6. Engagement with the District Assembly (DA) – questions related to directors’ relationship with the other sectoral departments of the MMDA 7. Devolution Transition Process (DT) –details about the 2012 devolution transition process and the perceived challenges and opportunities that emerged from that reform 8. Staffing and Resources (SR) – opinions and perspectives of the directors on the staffing and resource availability in their offices 9. Final Section (FI) – enumerator observations